Dealing with family conflicts in decision-making in end-of-life care of advanced cancer patients - Laryionava, Katsiaryna; Winkler, Eva C. (Current oncology reports, 2021)
Purpose of Review: The family plays a significant role in end-of-life care and decision-making with advanced cancer patients. This non-systematic review aims to summarize the family role and possible emerging conflicts and problems related to family involvement in decisions with advanced cancer patients. Recent Findings: Four important domains were identified: (1) discordance between patients and caregivers’ understanding of prognosis and goals of care; (2) internal family conflicts; (3) cultural differences regarding the role of the family in end-of life decision-making; (4) the burden on caregivers through caring for cancer patients. Summary: Based on the findings, we formulated some implications to consider for clinical practice. We suggest to involve the family in decision-making, to ascertain patients’ wish for family involvement and if necessary, taking a mediator role between patients and their caregivers; to be aware of “invisible” family influence on patients’ decisions; to assess systematically family burden and needs; to provide timely information, psychological support interventions and palliative care.